Filipino families' knowledge, attitude, practices on toxic pollution the case of two communities affected by lead pollution - Amparo, J. S. (Compendium of Human Ecology Researches in the Philippines, 2003)
The study was conducted to determine the knowledge, attitude and practices of community members were familiar with lead and aware of lead contamination in their area. The community members were familiar with lead aware of lead recycling industry adds problem to environments pollution and affects of human health negatively. Perceived health effects included lung problem, chest pain, dizziness and cough for men, children and pregnant women. Decreased educational performance for children and miscarriage for women. Decreased educational performance for children and miscarriage women were also perceived health effects of lead pollution. They showed favorable attitude to new pracitices in lead recycling industries, however, only few are willing to help improve the lead recycling industry and the clean-up of the area. Given these findings, there is a need to strengthen public education, integrate health and pollution issues development and land use plans, and do multi-stakeholder approach to site clean-up.